PENGARUH TAKARAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA KULTIVAR KACANG HIJAU (Vigna radiata L.) DI TANAH ENTISOL - Susu, Vebrianti Meni; Neonbeni, Eduardus Y; Ceunfin, syprianus (Savana Cendana, 2025)
This study aims to determine the response of three mung bean varieties to the correct dose of cow dung and to obtain the correct dose of cow dung for the growth and yield of three mung bean varieties. The design used in this study was a factorial randomized block design (RBD), 3 Ã— 3 Ã— 3. The first factor is the type of green bean variety, which consists of three levels, namely fore belu variety, wilzec variety, and mungo variety hepper. The second factor is the cow dung dose, which consists of 3 levels, namely 0 t / ha, 15 t / ha, 30 t / ha. The results showed that there is an interaction between the treatment of mung bean varieties and the treatment of the dosage of cow dung the initial observation of the soil temperature. The front belu mung bean had the highest plant growth and yield in terms of the highest plant height, the highest number of leaves, the highest dryness of the plants, the highest shell length, the highest weight of 100 seeds, the highest seed weight per plot and the highest harvest index. The dose of cow dung of 30 t / ha could change the growing environment and achieve the highest growth and yield effects. Mung bean varieties offer mixed growth and yield performance.